Are German National Accounts informationally efficient? - Roland Döhrn (Journal of Business Cycle Research, 2023)
National accounts are subject to major revisions. To improve the reliability of first release data, it is important to know whether subsequent revisions show systematic patterns. Or, in other words, whether national accounts are informationally efficient in the sense that all available information is incorporated into the data. This paper used annual data to test three dimensions of informational efficiency: weak efficiency, strong efficiency, and Nordhaus efficiency. The weak efficiency tests found GDP revisions to be noise, whereas revisions of several GDP components showed systematic patterns. Strong efficiency tests found covariations of GDP revisions with some indicators. Business survey results in particular have the potential to reduce the extent of revisions. Finally, Nordhaus efficiency tests found some indication of revision stickiness.
Keywords: C82; E01; E66; 330; National account; Data revision; Informational efficiency